Before George Eliot Marian Evans and the periodical press - Dillane, Fionnuala (Cambridge, United Kingdom Cambridge University Press, 2014)
"This interdisciplinary study discusses the significance of Evans's work as a journalist, editor and serial-fiction writer in the periodical press from the late 1840s to the late 1850s and positions this early career against critical responses to Evans's later literary persona, George Eliot. Author argues that Evans's association with the nineteenth-century periodical industry, that dominant cultural force of the age, is important for its illumination of Evans's understanding of the formation of reading audiences, the development of literary genres and the cultivation of literary celebrity"--Provided by publisher.
Machine generated contents note: Introduction: Marian Evans and the periodical press; 1. 'The character of editress': Marian Evans at the Westminster Review; 2. 'Working for one's bread': Marian Evans the journalist; 3. Staging 'Scenes' in Blackwood's Magazine: melodrama, narrative voice and the Blackwood's Man; 4. After Marian Evans: the importance of being George Eliot; 5. Last impressions: Marian Evans takes on her audience.
Includes bibliographical references and index.
Keywords: Eliot, George -- 1819-1880 -- Criticism and interpretation; Journalism -- Authorship -- History -- 19th century; Press -- England -- History -- 19th century; Periodicals -- Publishing -- England -- History -- 19th century